Mengembangkan Pengetahun Sains Bumi Dan Lingkungan Melalui Pembelajaran Project Based Learning - Rachma Audina Al Khanza; Reni Pawestuti Ambari Sumanto (Postgraduate, University of Mataram, 2025)
This research focuses on the understanding of science knowledge of children which is still considered low. The learning process still uses the lecture method and also LKPD. With this study, researchers aim to analyze the effectiveness of earth and environmental knowledge with the help of project-based learning at the age of 5-6 years. The type of research used uses pre-experimental research with a one group pretest and postest design. The population of this study used all group B children at RA Miftakhul Hidayah with a sample of 36 children using purposive sampling technique. Tests carried out using instruments in the form of observation sheets, Normality Test with pretest results of 0.221 and post-test results of 0.134 can be declared normally distributed. Then for the results of the N-Gain Test has a score on Meab of 77.31 with a percentage of> 76%, it can be concluded that with earth and environmental science knowledge in children aged 5-6 years through Project Based Learning learning in the effective category used.